The Rules of the Game: International Money in Historical Perspective - McKinnon, Ronald I.; Henning, Randall; Hussman, John P.; Herz, Bernard; Robinson, David; Schroder, Jiirgen; Williamson, John (Journal of Economic Literature, 2016)
NO WORLD CENTRAL BANK issues a separate currency for commerce across national boundaries. Instead, a system of national monies works more or less well in providing a medium of exchange and unit of account for current international transactions, as well as a store of value and standard of deferred payment for longer-term borrowing and lending. How do national governments and banking institutions interact to provide international money for merchants and investors? By necessity, this monetary interaction changes with time, place, political circumstances, and financial technology. To better understand its historical evolution, let us follow Robert Mundell and distinguish between a monetary system and a monetary order: